Development perspectives of the investment facilitation for development agreement - Axel Berger; Mina Mashayekhi; Marten Smeets (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
The WTO Investment Facilitation for Development Agreement (IFDA) offers significant development perspectives by speeding up and streamlining administrative procedures and reducing transaction costs. Domestic regulatory reforms, combined with comprehensive special-and-differential treatment as well as substantial technical and financial support are essential to ensure the beneficial implementation of the IFDA and sustainable and productive FDI.
Keywords: 330